Effect of Planting Distance and Chicken Mnure on Growth and Production of Okra (Abelmoschus esculentus L.) - Saiful Arifin; Al Machfudz WDP; Lydia Kusuma Ambarwati (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this study was to determine the effect of spacing and chicken manure on the growth and production of okra (Abelmoschus esculentus) plant. This research was conducted in April-June 2021 in Jiken Village, Tulangan District, Sidoarjo. The experiment was arranged in a factorial manner in a Randomized Block Design (RAK) consisting of 2 factors. The first factor is plant spacing, consisiting of: 25 x 50, 35 x 50, 45 x 50 while the second factor is chicken manure consisting of: on chicken manure, chicken manure 5 tons/ha and 10 tons/ha chicken manure. Observation variables consist of plant heigh, number of leaves. stem diameter, fruit number, fruit length, fruit diameter, fruit wet weight, fruit dry weight and harvest index. The data were analyzed by5% ANOVA followed by the Honest Significant Difference (BNJ) test at the 5% level. The result showed that there was a significant interaction between plant spacing and chicken manure on the observed variable of okra harvest index. Plant spacing treatment had no significant effect on the observed variables of plant heigt, number of leaves. stem diameter, fruit number, fruit length, fruit diameter, fruit wet weight and fruit dry weight. The application of chicken manure had a significant effect on the observed variables of plant height, number of leaves, stem diameter, number of fruit and harvest index. The combination of treatment spacing (45 x 50) and chicken manure at a dose of 10 tons/ha resulted in the highest growth and pcroduction of okra plants.